PENERAPAN EDUKASI FAMILY CENTERED MATERNITY CARE TERHADAP PERILAKU IBU POSTPARTUM MELALUI ASUHAN HOME CARE - Erinda Nur Pratiwi; Desy Widyastutik; Siti Nurjanah; Retno Wulandari (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia are higher than the other Southeast Asia countries. To solve these problems, the utilization of an appropriate educational model for postnatal women is required with involving the family as social support. This study aimed to analyze the effect of the implementation of the FCMC model on postpartum mothers' attitude in the puerperium care in the Public Health Center of Gambirsari Surakarta. The length of this study was approximately one year from January to Desember 2020. Wilcoxon test was used as the data was not normally distributed (p-value 0,000). There is an effect in the implementation of FCMC model on postpartum mother's attitude in postpartum perineal care. There is an effect in the implementation of FCMC model on postpartum mother's attitude in postpartum homecare.